Analysis Of Highest And Best Use For Vacant Land In Banjar Laplapan, Petulu Village, Ubud District, Gianyar Regency - Saraswati, I Gusti Ayu Prili; Kartika Yudha , I Made Endra (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Bali as a leading tourism destination has experienced significant growth in the tourism sector. Ubud, the cultural and spiritual center of Gianyar Regency, attracts domestic and international tourists. However, there are still vacant lands in the Ubud tourism zone that have not been optimally utilized, including an area of 2,700 m² in Banjar Laplapan, Petulu Village. This study aims to determine the most optimal land use using the Highest and Best Use (HBU) analysis which evaluates alternative land use based on physical possibilities, legal permits, financial feasibility, and maximum productivity. The research method used mixed method with Sequential Explanatory Design, evaluating three scenarios: villas, restaurants, and sports studios using Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). The results show that villa development is the most feasible choice with an NPV of IDR 639,557,915, an IRR of 57.83%, and a PP of 1.71 years. The restaurant scenario is still feasible with an NPV of IDR 162,038,471, an IRR of 54.26%, and a PP of 1.82 years. The sports studio scenario is not feasible with a negative NPV of -IDR 4,921,141,243, IRR -8.48%, and a PP exceeding 10 years. Based on the HBU criteria, villa development provides the highest value and is recommended as the best alternative.